Os Ducas e a recompensa dificilmente dividida - João Vicente de Medeiros Publio Dias (Medievalista)
The rebellion that brought the Komnenoi to power in 1081 was successful because it had many supporters, the most important of which was the Doukai, a lineage that had already controlled imperial power and with which Alexios was linked by marriage. The traditional position of historiography is that this was the beginning of an aristocratic government in which the emperor’s relatives enjoyed a share of power. However, more recent studies dispute the extent of the distribution of power under the Komnenoi (1081-1118), claiming that these emperors were more centralizing and traditional than previously thought. However, in fact, the emperors did distribute power, especially Alexios I (1081-1118), but in a more restricted and ad hoc way. Thus, given the Doukas’ role in the rebellion, it was expected that Alexios I would share power with this family, but he preferred to do so with his mother and brother. The Doukas, feeling aggrieved, spared no effort to gain a foothold in the regime, resulting in a series of internal crises that pitted various members of the family consortium that had seized power against each other. In the end, they were unsuccessful. However, this claim for shared power produced a parallel identity for the Doukas and corresponding discourses, which lasted after the death of Alexios I and continued to exist during the reign of John II (1118-1143). This identity emphasized the role of this family in seizure of power and the legitimization of the new emperor, as well as demanded space and power. This article will deal with these issues.